(untitled) (Research, Society and Development, 2022)
Inclusive education is, without a doubt, one of the biggest challenges of the developed society nowadays, because we believe that it involves much more than the person with disability, it also involves the family, school and society. This article proposes to analyze the social relations of the school environment and the coexistence between students with disabilities and teachers in the classroom and at school. For this study, in order to understand how special and inclusive education relationships happen, as well as the interactive circumstances that these students establish with their teachers, we adopted the proposal of a bibliographic research to guide the theme based on theorists and researchers in the area, as well as the documentary research involving the main documents of official matrix as a way to elucidate concepts that deal with special education in Brazil. As a result, based on information from the records of research carried out previously, it appears that the process of including people with special educational needs is still improving. Many problems need to be overcome for the effectiveness of inclusion in order to ensure that the person with disabilities can enter and remain in the school environment, having their specificities recognized and particularities respected. From this perspective, it is essential that the school, through continuing education, understand the complexity in which the specialized educational service is inserted, as well as the challenges that are posed to the school in the task of teaching all students.